Peranan Gembala Sidang bagi Pertumbuhan Jemaat di Gereja Lokal - Yohanes Twintarto Agus Indratno; Stefanus Dully; Yusup Heri Harianto (STT Bala Keselamatan Palu, 2022)
Abstract:The shepherd is the one who guides the congregation in pastoralism, certainly too short to teach how broad and deep the knowledge of God is. One of the most important things is that God Himself has laid down the task of caring for, nurturing, and educating the congregation into His power and calling. Shepherds who must prepare the congregation to live in favor of God. The purpose of this study is to explain the duties and roles of shepherds in faith-building or the so-called discipleship. Discipleship is a command of God called the great commission in Matthew 28:19 it says